miR-328-3p suppresses hepatocellular carcinoma progression by regulating HMOX1 expression - Weixing Wang; Jun Li; Changjun Pan; Deguo Wang; Jian Dong (Discover Oncology)
Abstract Introduction Most oncogenic genes contribute to cancer progression, but their role and regulatory mechanisms are not yet fully understood in hepatocellular carcinoma (HCC). This study aimed to explore the role of miR-328-3p and the regulatory relationship between miR-328-3p and HMOX1 in HCC. Methods We utilized Cox and LASSO regression to identify a panel of oncogenic genes associated with hepatocellular carcinoma (HCC) progression within the TCGA-LIHC cohort and the GSE104580 dataset. The expression levels of the hub gene, HMOX1, were assessed in HCC cell lines using qPCR. The functional roles of miR-328-3p and HMOX1 were evaluated through a series of in vitro assays, including CCK-8 for proliferation, colony formation, wound healing, and Transwell assays for migration and invasion. The direct interaction between miR-328-3p and HMOX1 was explored using a luciferase reporter assay, Western blot (WB) for protein expression analysis, and functional assays to determine the impact on cell proliferation and migration. Results Eight candidate genes (BIRC5, TNSF4, SPP1, HMOX1, ADM, RBP2, IGF1, and LECT2) were screen out. The hub gene HMOX1 among had high expression level in HCC cell lines. High HMOX1 expressing cell line had significantly increased proliferation and migration capacities. Moreover, HMOX1 was identified as a target of miR-328-3p, which regulated the HMOX1 expression in qPCR and WB assays. High miR-328-3p expressing HCC cell had diminished capacities for proliferation and migration. However, concurrent upregulation of HMOX1 expression resulted in enhanced proliferative and migratory abilities in these cells. Conclusion Our study has advanced our understanding of the roles of miR-328-3p and HMOX1 in HCC, demonstrating the inhibitory effect of miR-328-3p on the oncogenic activity of HMOX1. Hence, these results revealed the function of miR-328-3p and a novel mechanistic pathway for HCC and suggested the potential therapeutic targeting of miR-328-3p and HMOX1 for HCC intervention strategies.